y^(3) - 2y^(2) + 4y Factor out 'y' Hence y(y^2 - 2y + 4) This will not factor any further.
2y(3x + 1)
It is y+3y-2y = 2y simplified
5+y+2y? = 5+3y?
2y + 7x + y-1?
y^(3) - 2y^(2) + 4y Factor out 'y' Hence y(y^2 - 2y + 4) This will not factor any further.
2y(3x + 1)
-2y+y = -y
2y
(2y + 1) + (y^2 + 1) = 2y + 1 + y^2 + 1 = y^2 + 2y + 2
It is y+3y-2y = 2y simplified
5+y+2y? = 5+3y?
2y + 7x + y-1?
It is an ordinary linear equation. Divide by 2, solving for y, and you get y = 1.5x. This is a straight line that goes through the Y intercept 0, with a slope of 1.5.
To simplify Y plus Y, you can combine the like terms. In this case, both Y terms are like terms because they have the same variable. When you add them together, you get 2Y. Therefore, Y plus Y simplifies to 2Y.
1
9+2y=3 2y=-6 y=-3